The Implementation of Problem Based Learning Using Integrated Student's Worksheet (LKPD) Towards Student's Critical Thinking of 2nd Grade at SMP N 12 Padang - Lely Rahmianti (Universe, 2020)
This study aimed to reveal students critical thinking skills also to see the respons of students and teacher after using problem based learning and integrated students worksheet (LKPD). The type of this research was Quasi Experiment with a non-equivalent control group design. The population in this study were students of class VIII SMP N 12 Padang. Samples were taken using purposive samping and the sample in this study were VIII.4 as an experiment class and VIII.5 as a control class. The result of this study was an experiment class got high score than control class. This is evindenced by the avarege posttest of experiment class (77,12) and control class (73,83) the hypothesis test showed t-count (3,5) > t-table (1,67) and supported by positive respons of sudents and teacher. It can be concluded the implementation of PBL give significant effect to critical thinking students of 2nd grade at SMP N 12 Padang.